The Horse, the Wheel, and Language : How Bronze-Age Riders from the Eurasian Steppes Shaped the Modern World - Anthony, David W. (Book collections on Project MUSE., 2007)
Argues that the domestication of the horse and the use of the wheel by the prehistoric peoples of the central Eurasian steppe grasslands facilitated the spread of the Proto-Indo-European language across most of the ancient world.